Development and testing of potential indicators for evaluation of dairy production systems - PATEL, DIKSHA; PONNUSAMY, K; SENDHIL, R (The Indian Journal of Animal Sciences, 2019)
The present study classified the dairy production system of India based on its functional dynamism. The extent of functional dynamism of dairy sector in different states of India was determined using composite dairy production system index which was developed on the basis of optimum combination of 26 indicators by the method of principal component analysis. Twenty states which have major contribution in overall milk production of the country were selected and delineated into three categories, viz. dynamic, transient and subsistence dairy production systems. As per the indices score, the dairy production system of Kerala, Punjab, Goa, Haryana, Gujarat and Rajasthan were delineated as dynamic dairy production system. Tamil Nadu, Karnataka, Himachal Pradesh, Andhra Pradesh, Maharashtra, Madhya Pradesh, were categorized as transient dairy production system while Uttar Pradesh, Uttarakhand, Jammu and Kashmir, Odisha, West Bengal, Bihar, Chhattisgarh and Jharkhand states were grouped as subsistence dairy production system. The study implicates the necessity for increasing the milk production and productivity of bovines in West Bengal, Odisha and Goa by genetic improvement through crossbreeding, selective breeding and upgradation programmes. Increasing the area under fodder and pastures as well as fodder availability need further focus in Uttar Pradesh, West Bengal, Jharkhand and Bihar. States like Chhattisgarh, West Bengal, Bihar and Jharkhand need impetus in improving their veterinary infrastructure. Development of organized milk marketing and value addition network would further strengthen the dairy sector in all the states. Policy makers should concentrate on state-centric interventions to bring more dynamism in the dairy production system on the basis of identified gaps.